What education from zero to six years? Legislative perspectives and new cultural challenges for Italian educational services - Agnese Infantino (Universidade Federal de Santa Catarina, 2017)
The paper presents and analyzes the new perspective from the "Integrated Education and Education System from birth to six years" defined by Law 107/2015 and Decree No.65 of 2017. Early Childhood education for  toddler 0-3 and 3-6  pre school Childhood are an integrated system in which, starting with a new vision of the child from zero to six years, the theme of educational continuity and a pedagogical culture shared between "nursery" and pre school  will be of particular importance. The new law opens up important educational perspectives in the perspective of zero-six, but also raises new challenges, particularly regarding coordination and training processes of professional educators and teachers.